Evaluation of the outcome of sclerotherapy, complications and predictors of treatment success for venous malformations in hospital Kuala Lumpur - Yeh, Ding Chu (2023)
Introduction: Percutaneous sclerotherapy is often considered as the first-line intervention for patient with cutaneous venous malformations. Objective: To determine the outcome of percutaneous sclerotherapy for cutaneous venous malformation (VM) and predictors of positive response to treatment. Method: A total of 149 patients with venous malformation were treated in Hospital Kuala Lumpur during the 10 years span of 2010 to 2020. 88 patients were successfully recruited for the study, all of them were given the same questionnaire to answer regarding treatment outcome and patient satisfaction. Patient files and imaging data were retrieved to obtain demographic data and information regarding the VM treatment. Logistic regression was used to determine significant predictors to patient satisfaction. Result: Most common site of VMs is the head and neck region (76.1%). Majority of the patients presented with swelling (97.7%, n=86) as symptoms. Sclerotherapy is most efficient in managing swelling and aesthetic complaints, but not pain. In all, 65 (73.9%) patients satisfied with the sclerotherapy. Out of 207 total sessions, only one patient had major complication (Grade 3 CIRSE), most common complications are post-procedure swelling (78.4%). No positive predictors were identified. Conclusion: Percutaneous sclerotherapy using Sodium Tetradecyl Sulfate (STS) as the sclerosant is an effective treatment for venous malformation with minimum major complications. Nevertheless, it resulted in a high recurrence rate.